Hierarchically Controlled Inside‐Out Doping of Mg Nanocomposites for Moderate Temperature Hydrogen Storage. (24th October 2017) - Cho, Eun Seon; Ruminski, Anne M.; Liu, Yi‐Sheng; Shea, Patrick T.; Kang, ShinYoung; Zaia, Edmond W.; Park, Jae Yeol; Chuang, Yi‐De; Yuk, Jong Min; Zhou, Xiaowang; Heo, Tae Wook; Guo, Jinghua; et al.
Abstract: Demand for pragmatic alternatives to carbon‐intensive fossil fuels is growing more strident. Hydrogen represents an ideal zero‐carbon clean energy carrier with high energy density. For hydrogen fuel to compete with alternatives, safe and high capacity storage materials that are readily cycled are imperative. Here, development of such a material, comprised of nickel‐doped Mg nanocrystals encapsulated by molecular‐sieving reduced graphene oxide (rGO) layers, is reported. While most work on advanced hydrogen storage composites to date endeavor to explore either nanosizing or addition of carbon materials as secondary additives individually, methods to enable both are pioneered: "dual‐channel" doping combines the benefits of two different modalities of enhancement. Specifically, both external (rGO strain) and internal (Ni doping) mechanisms are used to efficiently promote both hydriding and dehydriding processes of Mg nanocrystals, simultaneously achieving high hydrogen storage capacity (6.5 wt% in the total composite) and excellent kinetics while maintaining robustness. Furthermore, hydrogen uptake is remarkably accomplished at room temperature and also under 1 bar—as observed during in situ measurements—which is a substantial advance for a reversible metal hydride material. The realization of three complementary functional components in one material breaks new ground in metal hydrides and makes solid‐state materials viable candidates for hydrogen‐fueled applications. Abstract : A new and innovative dual‐doping strategy is employed to magnesium nanocrystal system that demonstrates a reversible hydrogen storage at moderate temperature range with an unprecedented storage performance. This result makes a remarkable advance towards safe and efficient solid‐state hydrogen storage, and it can be adapted to both mobile and stationary fuel cell system to power a wide range of applications.